2018
DOI: 10.1111/pace.13328
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genetic variations in sodium channel subunits in a case of sudden infant death syndrome

Abstract: Genetic variation of both sodium channel and its modifiers may contribute to sudden unexplained death in childhood. However, the asymptomatic father suggests that genetic variation of these genes is not sufficient to cause sudden death or clinically detectable SCN5A phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Mutations in SCN5A are also causative of sudden infant death syndrome [438][439][440][441][442][443][444] as well as in channel ancillary subunits [445][446][447][448]. It is assumed that, as in the case of Brugada syndrome, an SCN5A/Na v 1.5 loss-of-function underlies sudden infant death.…”
Section: Sudden Infant Death Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in SCN5A are also causative of sudden infant death syndrome [438][439][440][441][442][443][444] as well as in channel ancillary subunits [445][446][447][448]. It is assumed that, as in the case of Brugada syndrome, an SCN5A/Na v 1.5 loss-of-function underlies sudden infant death.…”
Section: Sudden Infant Death Syndromementioning
confidence: 99%
“…It is assumed that, as in the case of Brugada syndrome, an SCN5A/Na v 1.5 loss-of-function underlies sudden infant death. In this context, Tan et al [446] described SCN3B and SCNB4 mutations that decreased peak I Na current but increased I NaL , whereas Neubauer et al [412] and Denti et al [447] identified a novel SCN1B mutations that decreased I Na density, providing thus plausible electrophysiological mechanisms underlying sudden infant death syndrome. Importantly SCN5A mutations in SIDS have also been identified in conjunction with other electrophysiological disorders, such as Brugada syndrome [356].…”
Section: Sudden Infant Death Syndromementioning
confidence: 99%
“…None had a history of cardiac arrhythmia or other cardiac presentation prior to death. While SCN1A [9,27], SCN1B [12,[35][36][37], and SCN5A [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Our literature review found 74 variants in 99 patients with SIDS, SIDS-like presentations, or SUDC affecting 72 different amino acid positions in a VGSC-related gene. 55/75 variants were present in SCN5A, reflecting in some cases the fact that this gene was specifically targeted in some series [13][14][15][16]20,21,24,46].…”
Section: Variant Position and Pathogenicitymentioning
confidence: 99%
“…The tissue-specific expression profiles of α-subunits and β-subunits are shown in Table 1. Variants in the cardiac-expressed SCN5A [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] gene are reported most frequently in association with SIDS and SUDC, but variants in SCN1A [9,27], SCN4A [34], SCN10A [35], SCN1B [12,[35][36][37][38], SCN3B [15,39] and SCN4B [39] have also for use under a CC0 license. This article is a US Government work.…”
Section: Introductionmentioning
confidence: 99%
“…Variants in the cardiac‐expressed gene SCN5A (Arnestad et al., 2007; Baruteau et al., 2017; Glengarry et al., 2014; Kato et al., 2014; Millat et al., 2009; Otagiri et al., 2008; Plant et al., 2006; Priori et al., 2000; Tester & Ackerman, 2005; Turillazzi et al., 2008; Wang et al., 2014; Wedekind et al., 2001; Winkel et al., 2015) have been reported in association with SIDS and SUDC. Variants in other VGSCs are only rarely identified in cases with SIDS and SUDC: SCN1A (Brownstein et al., 2018; Halvorsen et al., 2016), SCN4A (Männikkö et al., 2018), SCN10A (Neubauer et al., 2017) , SCN1B (Altshuler et al., 2012; Baruteau et al., 2017; Denti, n.d.; Hu et al., 2012; Neubauer et al., 2017), SCN3B (Tan et al., 2010; Winkel et al., 2015) , and SCN4B (Tan et al., 2010). Variants in epilepsy‐associated VGSC genes expressed in the central nervous system have also been associated with SUDEP: SCN1A (Cooper et al., 2016; Gal et al., 2010), SCN2A (Howell et al., 2015; Myers et al., 2018) , and SCN8A (Johannesen et al., 2018; Myers et al., 2018; Veeramah et al., 2012).…”
Section: Introductionmentioning
confidence: 99%